Bilingualism and the Serbo-German Bilingual Community of Serbs in Ingolstadt - Julijana M. Vuletić (University of Belgrade, 2020)
In this study we represent the bilingual language situation in the ethnolinguistic community of Serbs in Ingolstadt, recorded over the period of time from 2010 until 2013. The paper also addresses the occurrences of bilingualism and diglossia in the context of contact linguistics, their classification, as well as the samples of bilingualism in the researched corpus, with the accompanying phenomena of language contact. The obtained cross-section of the sociolinguistic and linguistic situation of the researched ethnolinguistic community, as well as the research results, refer to the specific community and specific corpus. Nonetheless, obtained results with certainty allow introspect into the life cycle dynamics tendency for the Serbo-German bilingual communities.  Reflecting upon the research results we may conclude that our investigated sample, which can expand onto the entire research corpus, can be regarded as being almost in the second last phase of the language change process. A rather significant part of the corpus in the further development of the language change process would certainly be the third generation of working migrants. Further direction of the bilingual community development will most likely be dependent upon this generation, as well as other accompanying factors.